Adsorption Properties of Silica with Chemically Bonded Amino and Guanidino Groups - T.M. Roshchina; V.Ya. Davydov; N.M. Khrustaleva; A.A. Mandrugin; K.B. Gurevich (Adsorption Science & Technology)
The influence of the non-homogeneity of the silica support and the nature and amount of modifier employed on the adsorption properties of materials with chemically bonded amino and guanidino groups was studied by means of gas chromatography (GC), adsorption measurements under static conditions and IR spectroscopy. The results indicate that adsorbents coated with a polymer film of amino groups have a nearly uniform surface. These adsorbents can be used for GC investigations and for the separation of polar compounds, including organic bases.